Steroid protection in aging and age-associated diseases - de Nicola, Alejandro Federico (2009)
Neuroactive steroids are secretory products of peripheral endocrine glands that modulate a variety of brain functions. A close relationship between neuroactive steroid structure and function becomes most evident under pathological circumstances. On one side, overproduction of glucocorticoid and mineralocorticoid neuroactive steroids may be detrimental to the hippocampus, which is enriched in glucocorticoid receptors (GR) and mineralocorticoid receptors (MR). Thus, a dysfunction of the adrenocortical system in aging and age-associated diseases (diabetes, hypertension) is able to cause hippocampal damage. Whereas aging and uncontrolled diabetes show a predominant GR overdrive, a MR overdrive characterizes hypertensive animals. Some abnormalities commonly found in the hippocampus of aging, diabetic and hypertensive animals include decreased neurogenesis, astrogliosis and neuronal loss in the hilus of the dentate gyrus (DG). On the other side, and in contrast to adrenal gland-derived steroids, estrogens qualify as hippocampal neuroprotectants. Given to middle-age mice, estrogens stimulated proliferation and differentiation of newborn cells in the DG, decreased astrogliosis and increased hilar neuronal number. Similar estrogen effects were obtained in mice with streptozotocin-induced diabetes and in spontaneously hypertensive rats (SHR). The results suggest that in aging and age-associated diseases, adrenocortical steroid overdrive sensitizes the hippocampus to the pathological milieu imposed by a pre-existing degeneration or illness. In this setting, estradiol neuroprotection rescues hippocampal parameters previously altered by the pathological environment.